Karakteristik Karkas Bandikut (Echymipera kalubu) di Kabupaten Manokwari: Carcass Characteristics of Bandikut (Echymipera kalubu) in Manokwari Regency - Frandz Rumbiak Pawere; John Arnold Palulungan (Fakultas Peternakan Universitas Papua, 2020)
The research purpose is to investigate the characteristics of bandicoot’s (Echymipera kalubu) carcass in the Manokwari Regency, West Papua Province. Thirty-two (32) bandicoots, with the age of ± 4-month-old, were used for this study, the subjects consisted of 16 males and 16 females. The research method used was the exploration method. The results showed that the bodyweight of males and females bandicoot was 1709.38 ± 506.31 g and 976.63 ± 296.11 g (P<0.05). Carcass weight of males and females bandicoot was 1339 ± 449.53 g and 738.22 ± 233.50 g (P<0.05) respectively. Carcass percentage of males and females bandicoot was 77.15 ± 6.24 % and 75.10 ± 4.32 % (P>0.05). The weight cut forequarter of males and females bandicoot was 614.85±221.87 g and 311.67±101.83 g (P<0,05). The weight cut of the hindquarter of males and females bandicoot was 768.76±377.66 g and 397.89±142.18 g (P<0,05). Fore carcass percentages of males and females bandicoot were 45.48±2.20 % and 42.39±3.50 % (P<0,05). Hind carcass percentage of males and females bandicoot was 56.22±12.22 % and 53.63±6.82% (P>0,05). In conclusion, there are differences in body weight, carcass weight, fore carcass weight, rear carcass weight, and the percentage of fore carcass weight between male and female Echymipera kalubu. On the other hand, there is no difference in the percentage of carcass and rear carcass percentage between male and female Echymipera kalubu.